Building automation : communication systems with EIB/KNX, LON and BACnet - Merz, Hermann; Hansemann, Thomas; Hübner, C. (Springer, 2018)
This book offers all important industrial communication systems for buildings in one single book! It stimulates a basic understanding of network and bus systems for the automation of buildings. After an introduction to EIB/KNX, LON und BACnet technologies, the authors illustrate how these systems can be utilized for specific applications, like air conditioning or illumination. This book assumes only a basic knowledge of mathematics and thanks to its simple explanations and many examples is ideal for students and professional engineers who require practical solutions. Numerous practical examples explain basic concepts of industrial communication technology as well as the procedure for the transmission of digital data. All chapters have been thoroughly revised for the 2nd edition and the book includes the latest technical developments and standards.- Resumé vydavatel
Keywords: automatizace budov; inteligentní budovy; digitální síť integrovaných služeb; environmentální inženýrství; building automation; intelligent buildings; Integrated services digital networks; environmental engineering; elektronické knihy; příručky; electronic books; handbooks and manuals